Les tables de mortalité - Bolduc, Jacques (Assurances)

(untitled) (HEC Montréal, 1986)
Our contributor, actuary Jacques Bolduc, examines certain problems presented by mortality tables and their contingent factors. He ends his article by stating that several life insurance companies establish their tarifs with an improvement in mortality rates in view; however, most companies use present mortality rates, ignoring all possibility of future improvement or deterioration. Until the end of the 1960's, a large part of the classic product of life insurance companies was devoted to savings and the premium charged to the client included an element which covered this savings. This increased the premium charged to clients, of which only a portion covered the cost of mortality. With inflation, the increase in interest rates and changes in the tax laws, trust companies and banks took a large part of the savings of individuals and insurance companies had to change their approach. The traditional life insurance product gave way to an insurance policy which, as a rule, contained little or no savings with the result that the part of the premium related to the cost of mortality took on greater importance.